Price Effects of Preferential Market Access : Caribbean Basin Initiative and the Apparel Sector - Özden, Çaglar; Sharma, Gunjan (Oxford University Press on behalf of the World Bank, 2013)
Preferential trade arrangements should be evaluated by their effect on prices rather than by their effect on the total value of trade. This point is emphasized in the theoretical literature but rarely implemented empirically. This article analyzes the U.S. Caribbean Basin Initiative's (CBI's) impact on the prices received by eligible apparel exporters. The CBI's apparel preferences are the most important and heavily used unilateral preferences because of high trade barriers imposed on exports from the rest of the world. A fixed effect generalized least squares (GLS) estimation is used to isolate the effects of other factors (such as quality, exchange rates, and transaction costs) and to identify the effects of tariff preferences. CBI exporters capture only about two-thirds of their preference margin despite the high degree of competition among importers. This translates into a 9 percent increase in the relative prices they receive, with some variance across countries and years. Countries specializing in higher value items capture more of the preference margin, and the implementation of the North American Free Trade Agreement (NAFTA) has a negative effect. Removing multifibre arrangement quotas significantly lowers the benefits of CBI preferences.